2011
DOI: 10.1038/hr.2011.168
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of photoplethysmographic and arterial tonometry-derived indices of arterial stiffness

Abstract: Arterial tonometry is a method to assess arterial stiffness and has become a valuable tool in the stratification of cardiovascular risk. The arterial tonometry-derived augmentation index (AIx) is a marker of arterial stiffness and an independent predictor of mortality. As the AIx is relatively cumbersome to obtain, simpler methods such as analysis of pulse waves obtained by digital photoplethysmography have been proposed to estimate arterial stiffness. The objective of this study is to compare the usefulness o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 25 publications
1
30
0
Order By: Relevance
“…Although the prognostic value of PWVcf is well established 6,8,9 and its use for cardiovascular risk assessment is recommended in clinical practice according to current guidelines, 35 SI has been associated with cardiovascular risk estimates only in few small studies. 21,22 The results of the present study showed that increasing SI and PWVcf by 2.2 m/sec (i.e. 1 SD, same for both indices) led to ca.…”
Section: Discussionmentioning
confidence: 88%
“…Although the prognostic value of PWVcf is well established 6,8,9 and its use for cardiovascular risk assessment is recommended in clinical practice according to current guidelines, 35 SI has been associated with cardiovascular risk estimates only in few small studies. 21,22 The results of the present study showed that increasing SI and PWVcf by 2.2 m/sec (i.e. 1 SD, same for both indices) led to ca.…”
Section: Discussionmentioning
confidence: 88%
“…Arterial stiffness was estimated by digital volume pulse (DVP) analysis as previously described and validated (Pulse Trace® PCA 2, CareFusion, Rolle, Switzerland) [10]. The device collects 6 representative pulse waveforms with a pulse interval close to the average pulse interval.…”
Section: Methodsmentioning
confidence: 99%
“…The analysis of the finger PPG waveform has been used as a non-invasive method to assess arterial stiffness [12,13]. PPG is a ubiquitous optical technique, based on the measurement of changes in blood circulation in the vascular bed of a tissue.…”
Section: Introductionmentioning
confidence: 99%